2007
DOI: 10.1002/polb.21282
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of an epoxy based thermoset containing a fluorinated thermoplastic

Abstract: A novel fluorinated thermoplastic (FT) was synthesized from diglycidyl ether of bisphenol A (DGEBA), and 3-(trifluoromethyl)aniline. FT was found to be miscible with DGEBA as shown by the existence of a single glass transition temperature (T g ) within the whole composition range. On the basis of several experimental techniques, it was found that upon heating etherification reaction takes place between FT and DGEBA. A DGEBA-aromatic diamine (4,4 0 -methylenebis(3-chloro 2,6-diethylaniline) formulation was modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The curve for FEP‐modified samples exhibits an increase in x gel with FEP concentration. This evolution of x gel is consistent with modification of the epoxy–amine stoichiometry induced by the etherification reaction 20…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The curve for FEP‐modified samples exhibits an increase in x gel with FEP concentration. This evolution of x gel is consistent with modification of the epoxy–amine stoichiometry induced by the etherification reaction 20…”
Section: Resultssupporting
confidence: 81%
“…For the DGEBA/FEP/MCDEA series (closed symbols), the dependence of T g on composition exhibits a similar trend to that observed for the DGEBA/TFA/MCDEA series. However, in this case the observed behaviour is the sum of at least two effects 20. On one hand, the FEP acts as a plasticizer independently of whether it is linked or not by chemical bonds to the epoxy–amine network.…”
Section: Resultsmentioning
confidence: 96%
“…Reaction of a perfluorinated epoxy (2,2,3,3,4,4,5,5,6,6,7,7,8,9,9,9-hexadecafluoro-8-trifluoromethyl nonyloxirane, FED3, Sigma-Aldrich) with a known excess of a di-amine (propyleneoxidediamine, Jeff, Huntsman). The reaction was performed in sealed tubes immersed in an oil bath, whose temperature was kept at 1008C for 120 min.…”
Section: Methodsmentioning
confidence: 99%
“…This might be because the fluorinated components in the curing systems (6FEP, 6FAPB) were low molecular weight molecules, such that, when curing, the functional fluorinated molecules were linked to the crosslinked network by covalent bonds, consequently, fluorine would not migrate. 14 The water absorption of the cured epoxy resins was determined and the results are summarized in Table 5. For all the four epoxy resins, the water uptakes determined by Method I were in the range of 0.35-0.40%, compared to those by Method II in the range of 1.10-1.36%.…”
Section: Mechanical Electrical and Dielectric Properties Of Cured Epmentioning
confidence: 99%
“…Fluorinated epoxy resins have many unique characteristics such as outstanding chemical resistance, improved toughness, good tribological properties, low dielectric constant, low moisture absorption, good optical properties and high thermal stabilities, etc. [10][11][12][13][14][15] Maier et al [16][17][18][19] reported several novel fluorinecontaining epoxy resins with low dielectric constants for potential microelectronic packaging applications. Hayward et al 20 reported that the fluorinated substitution reduced the water absorption of cured epoxy resins.…”
Section: Introductionmentioning
confidence: 99%